The effect of dexmedetomidine nebulization as a premedication prior to peripheral intravenous access in pediatric patients and its effect on separation anxiety score and acceptance to intravenous cannulation score. - D. M. Bonagua; H. C. Crisostomo; A. G. C. Hernandez; S. E. Brodit (Pediatric Anesthesia and Critical Care Journal, 2020)
Introduction Sedation in pediatric patients is one of the many chal- lenges in anesthesia practice. Premedication helps facili- tate smooth separation from the parents and ease the in- duction of anesthesia. Dexmedetomidine is a selective α- 2 adrenoceptor agonist that provides sedation, anxiolysis and analgesic effects without causing respiratory depres- sion. Nebulized dexmedetomidine application is a relatively non‐invasive, convenient and easy route of administra- tion that is well-tolerated by pediatric patients. Previous studies have established that intranasal dexmedetomidine effectively produced sedation, improved cooperation during invasive procedures such as intravenous cannula- tion and ameliorated separation anxiety in children with a dose range of 1-2 mcg/kg. This study was designed to evaluate the effect of dexme- detomidine nebulization as a premedication prior to pe- ripheral intravenous access in pediatric patients and its effect on ease of separation from the parent and ac- ceptance of intravenous cannulation. Materials and Methods A total of 52 children, aged 2 to 6 years and American Society of Anesthesiologists' (ASA) physical status clas- sification of I-II, scheduled for elective outpatient diag- nostic procedure were randomly allocated to receive ei- ther nebulized dexmedetomidine 2mcg/kg (Experimental group) or no interventional premedication (Control group). Sedation state was evaluated every 15 minutes af- ter premedication and behavioral state was assessed dur- ing separation from their parents and peripheral intrave- nous cannulation. The primary endpoint was the ac- ceptance of the venous cannulation and physical separa- tion from the parent. Results Both groups were comparable with respect to demo- graphic data (age, gender and comorbidities), weight, du- ration of procedure and duration of anesthesia. Vital signs were maintained within the normal range in both the groups during the whole peri-operative period, with nosignificant statistical difference between the two groups Intravenous cannulation acceptance was statistically sig- nificant between the groups, and was satisfactory in 18 patients (69.2%) in the experimental group but only in 6 patients (23.1%) in the control group. Likewise, ease of parental separation was statistically significant between the groups, and was satisfactory in 20 patients (76.9%) in the Experimental group and in 13 patients (50.0%) in Control group. Conclusion The use of nebulized dexmedetomidine (2mcg/kg) pro- duces satisfactory sedative effects that facilitate ease of successful intravenous cannulation, ease of children sep- aration from their parents, and is less likely to be associ- ated with perioperative adverse events.